1997
DOI: 10.1002/hep.510250116
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence after initial treatment in patients with small hepatocellular carcinoma

Abstract: able because the patients is a poor surgical risk, TAE has To assess intrahepatic metastasis (IM) and multicenbeen considered the treatment of choice. However, the value tric occurrence (MO) after initial treatment of small heof TAE is limited if the small HCCs have intracapsular or patocellular carcinomas (HCC) ß 2 cm in diameter, we extracapsular invasion. performed clinical and pathological studies in 112 pa-PEIT has been shown to be highly effective in patients with tients who underwent percutaneous ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(145 citation statements)
references
References 5 publications
7
135
1
Order By: Relevance
“…The risk factors for early recurrence have been reported to include tumor-related factors, such as vascular invasion and tumor size [23,24]. The present study also revealed that microvascular invasion was the only independent risk factor of 2-year recurrence after resection.…”
Section: Discussionsupporting
confidence: 68%
“…The risk factors for early recurrence have been reported to include tumor-related factors, such as vascular invasion and tumor size [23,24]. The present study also revealed that microvascular invasion was the only independent risk factor of 2-year recurrence after resection.…”
Section: Discussionsupporting
confidence: 68%
“…In Japan, 45-60% of recurrence after surgical resection was reported to be multicentric. Kumada et al [8] reported that 50.9% of recurrence after ethanol infection therapy was multicentric. However in China, Li et al [9] reported that the rate of multicentric recurrence after surgical resection was 30%.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] However, recurrence in the early HCC group generally occurred 3 years after surgery and was detected as a single nodule in a different segment, suggesting multifocal development of HCC. 12,17 Multicentricity, however, is probably not the sole cause of recurrence, since the cumulative 5-year recurrence rate (53%) in this group was higher than the rate of newly developed HCC (35%) in an at-risk cohort with cirrhosis alone.…”
Section: Recurrencementioning
confidence: 99%
“…This difference may be explained by a study showing that patients with a history of HCC are at greater risk of multicentric hepatocarcinogenesis than those without such a history. 15 It is possible that multifocal tumors or precursors may have become detectable at various times during postoperative follow-up.…”
Section: Recurrencementioning
confidence: 99%